(untitled) (Research, Society and Development, 2022)
The theoretical evolutions of scientific publications on the construct of territorial management demonstrate advances and declines over time. In this logic, the objective of this study was to evaluate the behavior of the theoretical evolutions of publications about the construct of territorial management over time. For this, bibliometry and its analysis tools were used, such as quantitative data and support software RStudio/Bibliometrix, QdaMiner and VOSviewer for bibliometric, geographic, social networks and text-mining analyses. Here, we conclude that environmental integration with socioeconomic framework enables the theoretical interrelations of territorial management in planning, management, organization and control in territorial decision-making. Publications involving the field of management, such as planning, management, organization and control for territorial decision-making, are theoretical elements that support publications over time. While in the field of territory, the theoretical elements that support the publications refer to natural resources, protected areas, territorial development and sustainable development.